Detection of NH3 in poultry housing based on tunable diode laser absorption spectroscopy combined with a micro circular absorption cell - Wang, Ke; Guo, Rui; Zhou, Yunhai; Jiao, Leizi; Dong, Daming (Frontiers in Physics, 2022)
Accurate monitoring of ammonia has decisive significance for the environmental control of poultry housing. Existing sensors based on semiconductor or electrochemistry have the defects of short life, severe baseline drift and delayed response when facing the harsh environment of poultry housing. In this work, we developed a portable sensor based on tunable diode laser absorption spectroscopy with a micro circular absorption cell for sensitive detection of ammonia in poultry housing. The micro circular absorption cell has a volume of only 25 ml, but the effective absorption path is up to 5 m, which allows the sensor to achieve the ability of less than 15 s response time and 0.2 ppm measurement accuracy. The results of continuous monitoring for 6 days showed that the ammonia concentration in the range of 0–6 ppm was accurately detected in a poultry house with 36 roosters. Through analyzing dynamic changes in ammonia concentration, we successfully identified some abnormal activity caused by humans or weather. Therefore, our sensor has performances of accurate, stable, real-time measurement of ammonia and can provide strong technical support for environmental control of poultry housing.